(untitled) (Orfeu, 2021)
In this essay I reflect on the presence of philosophy and poetry in Noel Rosa’s song. I am attentive to the way in which the composer articulates these two ways of positioning language before the needs of human expression and reflection. In my opinion, Noel Rosa uses poetry to make philosophy a daily heritage, accessible to the popular strata that he wanted to see included in Brazilian society. I develop my argument based on the song texts themselves, articulating them, when necessary, with the philosophical references they suggest, among so many: Socrates, Marx, Nietzsche, Schopenhauer, Heidegger. What is revealed as a result of this reflection is the vision of another path of depth in the fruitful and creative artistic process that Noel Rosa left us as a legacy that allows for constant enjoyment and learning.